The progress of american historical literature - Gibson, Elmer George (My University, 1896)
Introduction: Literature begins in man’s efforts to express the activities of life; thus the early expression of a people would naturally be those of events of families, colonies and states. But in the beginning the expression is necessarily rude, in that they efforts must be put into manual labor to provide shelter from the elements and sustenance from the latent soil. The labors of the founders of a state are rather to do than to think. Our forefathers came to a land that conquest gave no homes, cultivated fields, waving vineyards, shacks, or overflowing granaries, and these necessities were to be had only from incessant toil. The colonies being thus absorbed in the struggle for life, handed to the mother country for the higher activities of life—for the food of thought.
Citation: Gibson, Elmer George. The progress of american historical literature. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Literature; English; American; United states; Theses; Manuscripts (documents)